Evaluation of the Protective Properties of Amlodipine, on Cisplatin Induced Cardiotoxicity in Male Rats (Global Journal of Medical Research, 2013)
This study was aimed to evaluate the cardiotoxicity of cisplatin in rats and to investigate the cardioprotective effect of amlodipine on cisplatin treated rats by using cardiac biomarkers troponin, CK-MB. Thirty five healthy male swiss albino rats were used in this study. The study design was divided into two patterns: Pilot study design: The animals were randomly divided into two groups, In the first treated group, all rats received cisplatin in a single dose, while in the second treated group, rats received cisplatin in four divided doses every 2 days. Active study design: The animals were randomly divided into 3 groups (7 rats/ group) and treated as follows:- a- Normal saline (N.S) treated group. b- Cisplatin treated group. c- Amlodipine treated group with cisplatin. Blood samples were collected and used to determine the biomarkers serum troponin, CK-MB. The result from pilot study shows that in cisplatin treated groups (single dose) serum troponin, CKMB are not significantly change with control group. While, when we give cisplatin in multiple doses, there is a significantly increase in serum troponin, CK-MB. Amlodipine show a potent cardioprorective effect against cisplatin cardiotoxicity.
Keywords: cisplatin; amlodipine; cardiotoxicity; troponin; CK-MB